Association Between Lip Prints and Blood Groups Among Koya University Students - Harem Othman Smail; Rezhna Khder Hassan; Helin Omer Ismail (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Lip prints, also known as cheiloscopy, are designs created by the positioning of creases and lines around the red edge of a person’s lip. In forensic science, lip prints can be used for identification just like fingerprints. Blood is categorized into blood groups, sometimes called blood types, according to whether or not specific antigens are present on the surface of red blood cells. The aim of this project was to discover the correlation between lip prints and blood groups. A study involving 334 volunteers aged 18-25, collected at Koya University, used standard blood typing methods to determine their blood groups. Our results discovered a correlation between lip prints and blood groups in females; there is a correlation, but in males, there is not a correlation. The research indicates a correlation between blood groups and lip print patterns, suggesting that lip print traits may be linked to blood groups in females.